(untitled) (Acta Judicial Journal, 2022)
In this article we will try to analyze the evolution in the application of art. 59 CP. We will see its most remote origins, its current wording given by the 1995 Penal Code, the milestone set by STS 1045/2013 and the successive judgments that the High Court has issued on this matter until this year 2021.